2017
DOI: 10.21767/1791-809x.1000488
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Parity and Breastfeeding with Breast Cancer: A Review

Abstract: Background: The association between parity and breastfeeding with breast cancer is still conflicting. Therefore, we did an analysis to summarize the recent studies of breast cancer with the subject of parity and breast-feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Meta-analytic surveys focusing on breast cancer and reproductive variables in population-based studies confirmed that nulliparity, lactation and late age at first birth are significant independent determinants of breast cancer risk. 41,42 On the other hand, other studies from developing countries failed to emphasize that the age factor specifically at first child birth was significant. 43 Among African-American patients, it was documented that age had a dual effect on parity as a risk factor; increasing the risk in women younger than 45 years and decreasing it among those 45 years and older; thus highlighting some of the factors responsible for the observed variations in the incidence of breast cancer in these societies.…”
Section: Discussionmentioning
confidence: 93%
“…Meta-analytic surveys focusing on breast cancer and reproductive variables in population-based studies confirmed that nulliparity, lactation and late age at first birth are significant independent determinants of breast cancer risk. 41,42 On the other hand, other studies from developing countries failed to emphasize that the age factor specifically at first child birth was significant. 43 Among African-American patients, it was documented that age had a dual effect on parity as a risk factor; increasing the risk in women younger than 45 years and decreasing it among those 45 years and older; thus highlighting some of the factors responsible for the observed variations in the incidence of breast cancer in these societies.…”
Section: Discussionmentioning
confidence: 93%
“…On the contrary, it was also reported that multiparity appeared to increase the threat of ER/PR/HER2 negative BC. 26 However, the study 27 also revealed that parity increases the risk of hormone receptor-negative BC, whereas breastfeeding lowers the risk or lessens the unfavourable effect of parity. This is inconsistent with the current research; we had more hormone positive and HER2/neu negative tumours.…”
Section: Discussionmentioning
confidence: 98%
“…With an increase in the production of prolactin, women are less exposed to ER. 30 Other studies have stated that the blood ER levels of nursing women gradually increase after the last birth and continue to increase for several years until they reach the nulliparous state. 3 A study in 2002 analyzed the role of reproductive factors in breast cancer occurrence.…”
Section: Prolonged Interval Between Menarche and First Pregnancymentioning
confidence: 98%